H. G. Koenigsberger, Dominium regale or dominium politicum et regale. Monarchies and Parliaments in Early Modern Europe, London 1975 - Izdebski, Hubert (Czasopismo Prawno-Historyczne, 1977)
Recenzja: H. G. Koenigsberger, Dominium regale or dominium politicum et regale. Monarchies and Parliaments in Early Modern Europe. Inaugural Lecture in the Chair of History at University of London King's College 25th February 1975, [London 1975], s. 28.